Exploring The Impact of Green Accounting and Corporate Social Responsibility Disclosure on Firm Value Through Profitability In Mining Companies In Indonesia - Murdianingrum, Sri Luna; Zuhrohtun, Zuhrohtun; Mulyanto, Indro Herry; Susanto, Heri; Maradidya, Alfistia; Maheresmi, Handani (Asian Journal of Social and Humanities, 2024)
This study is dedicated to examining how the implementation of green accounting and the disclosure of corporate social responsibility impact the value of mining companies in Indonesia through profitability. Green accounting is a relatively novel area of research in Indonesia, particularly in the context of the mining sector. Given the ongoing governmental reforms in the mining industry, with the prohibition of raw material exports under Law Number 3 of 2020 amending Law Number 4 of 2009 on Mineral and Coal Mining, the study finds it intriguing to explore the implications of green accounting. The ban on nickel ore exports, as stipulated by the aforementioned legal amendments, sparked strong opposition from the European Union, leading to Indonesia being taken to the World Trade Organisation (WTO) in early 2021. This policy aligns with the broader objective of downstreaming, which seeks to secure a domestic supply of raw materials for mineral processing and refining, thereby mitigating adverse environmental effects. To initiate the research, the first step involves gathering data on pertinent variables from the financial statements of mining companies listed on the Indonesian Stock Exchange (IDX). Subsequently, SPSS will be employed to conduct tests and assess the influence of green accounting and corporate social responsibility disclosure on firm value, with profitability acting as a mediating factor.